"We don't want to be the bad guys": Oil industry's sensemaking of the sustainability transition paradox. (October 2022) - Halttunen, Krista; Slade, Raphael; Staffell, Iain
Abstract: The operating model of the global oil industry is not compatible with the goals of the Paris Agreement. For the industry, there is a fundamental tension between two competing mandates: the pressure to contribute to the social goal of climate change mitigation, and the need to perform financially and meet obligations to shareholders in activities that directly contribute to climate change. To explore the range of responses to the tension, we interview professionals from large international oil companies who work or have worked in climate related roles. This is novel data from a professional group that has not previously been interviewed in depth about climate change. We develop a framework of six archetypical responses to tension within the oil industry. Examples of strategic responses include accepting the paradox to choose priorities other than climate change mitigation and confronting the paradox to demand changes to the way the oil industry operates. Examples of defensive responses include the transfer of responsibility and projection of tension to other stakeholders. Responses calling for change in the oil industry are the most common among people who have left the industry and the least common for participants from companies headquartered outside of Europe. In a field marked by controversies and value-based debates, a better understanding of the views of people working on the energy transition inside the oil industry provides new insight into the discussion about possible routes to the sustainability transition. Highlights: Oil industry business model contradicts the need to mitigate climate change. Professionals have different ways of making sense of the paradoxical situation. We identify three strategic and three defensive responses to tension. Responses are influenced by different oil companies' cultures. Responses reveal logic behind arguments used in the oil-climate debate.